Effect of the addition of backing support plates on the shear strength of aluminium and steel adhesively bonded joints - A.I. Putra; S. Sugiman; A.D. Catur; H. Ahmad (Dinamika Teknik Mesin, 2025)
The use of adhesive joints has been increasing in joining metallic and non-metallic materials due to advantages such as homogeneous stress distribution and a smooth surface appearance. This study aims to analyze the effect of support plates on the shear strength of aluminium and steel adhesively bonded joints. The position of the Ã‚Â support plates was studied within the overlap area. Experimental testing was carried out using single lap joint specimens per ASTM D1002. Finite element modelling was also carried out using Abaqus software to analyze the stress distribution in the adhesive layer. The experiment results showed that the addition of the support plates did not increase the shear strength of the joint, but instead tended to decrease it. The strength of aluminium joints with support plates at a distance of 3.125 mm from the end of the lap of the joint decreased by 62%, while the strength of steel joints decreased by about 38%. Finite element modelling results show that von Mises stress at the end of the lap joint decreased with the addition of support plates.